A Broadband Half-Mode Substrate Integrated Waveguide Cavity Antenna with Triple Resonances - Astuti, Dian Widi; A. Majid, Huda; Alam, Syah; Setyawan, Andri (2025)
A simple, low-profile, compact, and broadband antenna is presented in this paper. The compact antenna is achieved through a 50% miniaturization of a full-mode substrate-integrated waveguide (FMSIW) antenna, known as half-mode substrate-integrated waveguide (HMSIW). The low-profile antenna is the result of the thin substrate thickness. However, the miniaturized and low-profile antenna suffers from narrow impedance bandwidth, which limits its application in antenna implementations. To address this issue, this paper proposes a broadband antenna in a single HMSIW cavity, offering a simple solution. The broadband performance is achieved by the merging of triple resonances. These triple resonances are generated by the combination of TE101, TE102, and TE202 modes, which are induced by a semi-rectangular ring slot on the top layer of the cavity. Good agreement is observed between the simulation and measurement results. The simulated fractional bandwidth (FBW) is 29.53% (9.67–13.02 GHz), while the measured FBW is 32.05% (9.51–13.14 GHz). Two identical antennas with different polarization directions are obtained by mirroring one of them to the other.